EXPERIMENT ON CREATION OF OPTIMAL AIR PROTECTION SYSTEMS IN ELECTRODEPOSITION - Vladimir L. GAPONOV; Vladimir I. GARSHIN (Advanced Engineering Research, 2010)
Research results of the regime parameters of the process installation and application experience of the combined security facilities of the operating space from harmful electrolyte emissions in agricultural engineering are offered.